2011
DOI: 10.1051/0004-6361/201117334
|View full text |Cite
|
Sign up to set email alerts
|

Detailed study of the X-ray and optical/UV orbital ephemeris of X1822–371

Abstract: Aims. Recent studies of the optical/UV and X-ray ephemerides of X1822-371 have found some discrepancies in the value of the orbital period derivative. Because of the importance of this value in constraining the system evolution, we comprehensively analyse all the available optical/UV/X eclipse times of this source to investigate the origin of these discrepancies. Methods. We collected all previously published X-ray eclipse times from 1977 to 2008, to which we added the eclipse time observed by Suzaku in 2006. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
45
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 23 publications
(54 citation statements)
references
References 12 publications
(18 reference statements)
9
45
0
Order By: Relevance
“…Iaria et al (2011) obtaineḋ P orb = 1.59(9) × 10 −10 s/s from the combined X-ray/optical/UV data set, consistent with the previous measurements. A similar value of the orbital period derivative (Ṗ orb = 1.3(3) × 10 −10 s/s) was independently obtained by Jain et al (2010) by analysing data in the X-ray band.…”
Section: Introductionsupporting
confidence: 89%
See 3 more Smart Citations
“…Iaria et al (2011) obtaineḋ P orb = 1.59(9) × 10 −10 s/s from the combined X-ray/optical/UV data set, consistent with the previous measurements. A similar value of the orbital period derivative (Ṗ orb = 1.3(3) × 10 −10 s/s) was independently obtained by Jain et al (2010) by analysing data in the X-ray band.…”
Section: Introductionsupporting
confidence: 89%
“…Although we find the same spectral shape reported by Iaria et al (2001), in this work we will give a different interpretation of its origin in light of the recent results reported by Burderi et al (2010), Bayless et al (2010), andIaria et al (2011), which showed a large derivative of the orbital period of X1822-371. Burderi et al (2010) showed that the large orbital-period derivative of X1822-371 indicates that the system accretes at the Eddington limit.…”
Section: The Continuum Emission and Presence Of An Optically Thin Adcsupporting
confidence: 60%
See 2 more Smart Citations
“…Its value is obtained by fitting a Gaussian to the partial eclipse profile, plus a function (e.g. a polynomial, sinusoidal function) to model the smooth modulation (Iaria et al 2011). After more than 30 years of tracing the orbital evolution, the orbital period change rate was reported to be 1.59(9)×10 −10 s s −1 , which is three orders of magnitude greater than the theoretical prediction based on the mass conservation in the binary system (Iaria et al 2011).…”
Section: Eclipsing X-ray Sourcesmentioning
confidence: 99%